HOW CORPORATE CULTURE DRIVES ENVIRONMENTAL PERFORMANCE THROUGH INNOVATION AND STRATEGIC ORIENTATION IN INDONESIA'S MSME SECTOR? (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
This study aims to examine the effect of owners' personal values, reflected in corporate culture, on environmental performance among Indonesia's MSMEs, with innovation and strategic orientation serving as mediating variables. The sample population comprised food and beverage MSMEs in Java Island, Indonesia. The survey was conducted on the island of Java. A self-administered questionnaire was used to collect data. The study employed PLS-SEM for analysis. The research results show that corporate culture has a positive and significant influence on environmental performance both directly and indirectly through strategic orientation. An interesting finding was that innovation orientation had a negative, insignificant influence on environmental performance, both directly and as a mediating variable in the relationship between corporate culture and environmental performance. This study contributes by proposing a multi-mediation model linking corporate culture and environmental performance through strategic orientation and innovation in the context of MSMEs. It provides empirical evidence from food and beverage MSMEs in Indonesia that strategic orientation plays a more decisive mediating role than innovation orientation in improving environmental performance. JEL: M14, Q56, L26.